Polanyi's Embeddedness and Shareholder Stewardship: A Contextual Analysis of Current Anglo-American Perspectives on Corporate Governance - Talbot, Lorraine E. (Social Science Research Network, 2012)
Polanyi saw the economy as properly embedded in society and argued that the capitalist free market, in commodifying social relations of production, seeks to disembed the economy from society. The resulting lack of continuity between society and economy, he maintained, created conflict which necessarily required state intervention. The market economy, therefore, in contrast to neoclassical/neoliberal economics’ vision of an autonomous, self-regulating market, required more, not less, state intervention to sustain it than alternative, more embedded economies. This article explores this conflict in the context of a specific neoliberal claim: that institutional shareholders are capable of being good “stewards” of the companies in which they invest. Utilising Polanyi’s embeddedness, this article assesses the “stewardship” approach as it is manifested in the US and in the UK. This approach is posited on a vision of a disembedded, self-regulating market. Putting it into practice is thus a retrograde step which will only exacerbate the problems created by the market-based corporate governance strategies which have prevailed since the late 1970s onwards.
Law
Keywords: Polanyi; conflict; crisis; embeddedness; shareholder stewardship